Communal and exchange relationship perceptions as separate constructs and their role in motivations to donate - Johnson, Jennifer Wiggins; Grimm, Pamela E. (Journal of Consumer Psychology, 2010)
AbstractResearchers have operationalized communal and exchange relationship perceptions as either mutually exclusive categories or opposite ends of a continuum. This research conceptualizes these relationships as distinct constructs that should be measured separately. We develop multi‐item measures of communal and exchange relationship perceptions and find that they are actually positively correlated. We also examine the way communal and exchange relationship perceptions combine to influence intrinsic, extrinsic, and social motivations to donate, a category stipulated in economics, but not in psychology. We find that both relationship perceptions influence consumer attitudes toward donating through a mix of intrinsic, extrinsic, and social motivations.